THE ROLE OF PROACTIVE MARKETING IN ENHANCING CUSTOMER LOYALTY: AN APPLIED STUDY OF THE OPINIONS OF A SAMPLE OF CUSTOMERS AT THE GREEN APPLE STORE IN BAGHDAD - Afrah Raheem Idan; Roaa Abdul Kareem Sahib; Zaki Muhammad Abbas; Saif Ali Al- Mofraje (Scholar Express Journals, 2022)
The aim of the current study is to measure the role of proactive marketing represented in (proactive orientation toward clients, pro-active orientation of competitors, market-based innovation) in enhancing customer loyalty represented in (the intention of the spoken word, the intention of redealing, the lack of sensitivity to price, and the behavior of the complaint) of a sample of customers in the green apple store in Baghdad. The survey tool was used to measure the level of proactive marketing availability and customer loyalty in the sample studied, as 350 questionnaire forms were distributed in cooperation with store staff, and he recovered 323 forms, after tabulating data, it was found that the number of forms that are valid for analysis reaches 309, which means that the response rate is 88.3%. In addition, the study seeks to achieve the conclusions it seeks to answer by adopting a set of statistical tools such as natural distribution, alpha-chronous coefficients, arithmetic mean, standard deviation, Pearson correlation coefficient (SPSS.V.27), and regression coefficients extracted under the amos.V.27; Consequently, the study concluded that there is a relation of statistical significance between proactive marketing and client loyalty. This contributed to reaching a set of important conclusions related to the targeted store, the most prominent of which was the focus of the studied store on achieving excellence in its products through increasing its preemptive marketing capabilities and attracting as many customers as possible. This helps increase customer value by building positive customer relationships and ensuring customer satisfaction and loyalty
Keywords: Proactive marketing,; Customer Loyalty.